Teaching strategies developed by English teachers to improve students writing and reading skills of the eigth year of the general basic education of Ing. José Corsino Cárdenas, Ing. Eduardo Pazmiño Barciona and Técnico Nacional Pasaje high schools in Pasaje city of the academic year 2010 - 2011. - Malla Velepucha, Mayra Rocio (2011)
English has become the means of all relevant social interactions and the ability to use English effectively is considered essential for today´s everyday happenings.